2014
DOI: 10.1080/2153599x.2014.880069
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological correlates of forgiveness

Abstract: A recent study of individuals with traumatic brain injury suggests that forgiveness is a neurologically based function related to decreased self-orientation associated with decreased right parietal lobe (RPL) functioning. The current study attempted to replicate these results using 23 individuals with diagnosed seizure disorders. Neuropsychological tests of bilateral frontal, temporal, and parietal lobe functioning were used as indices of cerebral integrity and correlated with a self-report measure of forgiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Further research regarding the expression of increased and decreased self-orientation processes is also warranted given the multiple studies that suggest that decreased RPL functioning (as measured by the JOLO and/or finger agnosia tests) is associated with increased transcendence (Johnstone et al, 2012;Johnstone & Glass, 2008) and increased willingness to forgive (Johnstone et al, 2012;Johnstone et al, 2014), but decreased empathy (Grattan et al, 1994;current study). Future research may benefit from determining how increased and decreased self-orientation may be related to other human experiences (e.g., altruism, antisocial personality, etc.…”
Section: Limitations and Future Directionsmentioning
confidence: 89%
See 1 more Smart Citation
“…Further research regarding the expression of increased and decreased self-orientation processes is also warranted given the multiple studies that suggest that decreased RPL functioning (as measured by the JOLO and/or finger agnosia tests) is associated with increased transcendence (Johnstone et al, 2012;Johnstone & Glass, 2008) and increased willingness to forgive (Johnstone et al, 2012;Johnstone et al, 2014), but decreased empathy (Grattan et al, 1994;current study). Future research may benefit from determining how increased and decreased self-orientation may be related to other human experiences (e.g., altruism, antisocial personality, etc.…”
Section: Limitations and Future Directionsmentioning
confidence: 89%
“…Two recently published studies suggest that decreased RPL functioning is also related to increased willingness to forgive in populations with both traumatic brain injury (TBI; Johnstone et al, 2012) and seizures (Johnstone et al, 2014). These studies suggest that to forgive, one must be willing to decrease focus on the perceived wrong to the self.…”
Section: Right Hemisphere Self-orientation and Empathymentioning
confidence: 99%
“…Dysfunction of IPL will cause an individual to be more emotional egocentricity because of disabling to perceive the emotions of others (Silani et al, 2013 ). Recent studies examined the association between neuropsychological indices of cerebral integrity and forgiveness in a population with traumatic brain injury (Johnstone et al, 2012 , 2015 ) and found that decreased parietal lobe functions were negatively related to individual differences of forgiveness. Taking someone else’s perspective is an important prerequisite for understanding and predicting other people’s mental states like desires, thoughts or intentions.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, although several studies have suggested the involvement of structural temporal lobe abnormalities in religiosity, the findings are inconclusive: on the one hand, temporal lobe atrophy has been associated with increased religiosity by using a region‐of‐interest (ROI) analysis (Chan et al., ; Owen, Hayward, Koenig, Steffens, & Payne, ), while another study found that higher religiosity was associated with an increased volume of the temporal lobe, also by using an ROI voxel‐based morphometry (VBM) analysis (Kapogiannis, Barbey, Su, Krueger, & Grafman, ). Similarly, whereas several neuropsychological lesion‐based studies have shown that damage to the inferior parietal lobe (IPL) is associated with increased spirituality (Johnstone, Bodling, Cohen, Christ, & Wegrzyn, ; Johnstone & Glass, ; Johnstone et al., ; Urgesi, Aglioti, Skrap, & Fabbro, ), another VBM study found that an increased IPL volume was associated with higher spirituality (Van Schuerbeek, Baeken, De Raedt, De Mey, & Luypaert, ). Thus, the debate on the precise neural mechanisms involved in religiosity is far from settled.…”
Section: Introductionmentioning
confidence: 99%
“…He found that peak experiences of absolute unity are associated with a reduced blood flow to the superior parietal lobes and an increased activation of prefrontal areas, which he interpreted as being associated with a stronger focused attention. Other studies have used neuropsychological assessment techniques as an indirect proxy for superior parietal lobe functioning to establish a relationship between parietal lobe atrophy and religiosity (Johnstone & Glass, ; Johnstone et al., , ; Urgesi et al., ). These studies indicate that a reduced activation or an impaired functioning of the parietal lobes (including the bilateral SPL and the IPL) is associated with a higher sensitivity for having spiritual experiences and increased religiosity.…”
Section: Introductionmentioning
confidence: 99%